Visual Thinking Processes and Interactions of Sixth Grade Students - Suna Çöğmen; Necla Köksal (Anı Publishing, 2019)
A cognitive psychologist Abigail Housen focuses on what people think while they are looking at a piece of art through the inevitable relationship between thinking and language. In this context, from the five viewer patterns, Housen and Yenawine developed a curriculum named Visual Thinking Strategies (VTS) which is for the first two viewer patterns called as Beginner Viewers. Current study aimed to examine the visual thinking processes and interactions of the students in a learning environment where VTS are implemented. As a case study, 6th grade students participated in a total of 10 sessions of VTS practices. The data was analysed using the content analysis and three themes named accountive viewer, constructive viewer and interaction were constructed. Beginner viewers' characteristics, increasing interaction, and interest to the works of arts were observed among the participants. Future studies might examine the development of various skills in the settings where VTS is implemented.